THE INFLUENCE OF STYLE TENDENCIES OF WORLD CULTURE ON THE DESIGN OF CHILDREN’S BOOKS - Гула, Є. П.; Денисенко, К. В.; Дульська, Я. О.; Оганесян, С. В. (Art and Design, 2023)
Purpose: analyze the influence of stylistic trends that dominated in certain periods of cultural history, on the style of children’s books. Methodology. Methods of observation, historical-typological, iconographic, image-stylistic analysis, and comparative analysis are used. Results. The influence of dominant styles in certain historical periods on the design of children’s books has been studied. It was found that most of the styles of architecture, fine arts, and other spheres of creative activity, and became the leading styles of their time, had some influence on the style of children’s books. The design style of children’s publications influenced from the styles that were dominant in time of the production of the book, as well as various historical and ethnic styles of the past, to create a certain informational and psychological support of the text of the book. Scientific novelty. The influence of styles that dominated in certain historical periods on the design of children’s books is revealed. The hypothesis that different types of artistic creativity have a mutual influence on the principles of formation and reflection of leading stylistic features is confirmed. It is noted that the influence of dominant styles from various fields of art is sometimes so strong that the use of their style-forming principles, such as in design of children’s books, can lead to both positive and negative consequences. Practical significance. The results of the research can be used by illustrators and graphic designers in practical work, as well as in the educational process of training these specialists, and in further research.